2007
DOI: 10.5433/1679-0359.2007v28n2p269
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados à infecção pelo vírus da diarréia viral bovina na região Sul do Rio Grande do Sul

Abstract: ResumoO presente estudo teve como objetivo estimar a prevalência e determinar os principais fatores associados à infecção pelo vírus da diarréia viral bovina (BVDV) no rebanho bovino dos municípios de Santa Vitória do Palmar e Chuí, na região sul do estado do Rio Grande do Sul. Amostras de soro foram submetidas à prova de soroneutralização e, em cada propriedade avaliada, aplicou-se um questionário epidemiológico para investigar fatores que poderiam estar associados à infecção. As amostras de soro foram coleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
19

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 10 publications
3
15
0
19
Order By: Relevance
“…The high number of herds that had at least one reagent animal (100.0%) is similar to the results reported by Fino et al (2013) in the state of Santa Catarina and compatible with the 82.4% found in Rio Grande do Sul (QUINCOZES et al, 2007) and with the 97.6% found in the state of Maranhão (CHAVES et al, 2012). These results could be associated with inadequate procedures of sanitary management on the family farms in question, resulting in the introduction of viremic cattle (acute infection or PI).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The high number of herds that had at least one reagent animal (100.0%) is similar to the results reported by Fino et al (2013) in the state of Santa Catarina and compatible with the 82.4% found in Rio Grande do Sul (QUINCOZES et al, 2007) and with the 97.6% found in the state of Maranhão (CHAVES et al, 2012). These results could be associated with inadequate procedures of sanitary management on the family farms in question, resulting in the introduction of viremic cattle (acute infection or PI).…”
Section: Discussionsupporting
confidence: 88%
“…The presence of heterologous species in breeding systems can influence the serological diagnosis, given that some species are susceptible to pestiviruses (PASSLER; WALZ, 2009). Quincozes et al (2007) observed that the presence of sheep in consortium breeding systems has been considered a risk factor for the presence of anti-BVDV antibodies. Meanwhile, Chaves et al (2012) reported that pig breeding is a statistically significant risk factor for BVDV seropositivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foram realizados, também, inquéritos sorológicos nos estados de São Paulo, Rio de Janeiro, Minas Gerais, Goiás, Rio Grande do Sul, Santa Catarina, Paraná, Mato Grosso do Sul, Distrito Federal, Ceará, Bahia, Sergipe e Maranhão, que comprovaram que o vírus está disseminado na população bovina do país (vIDor et al, 1995;PItuco et al, 1997;QuIncozes, 2007;sousa et al, 2009).…”
unclassified
“…In Brazil, the presence of BVDV has already been proven in several states, such as Pernambuco [166], Goiás [167], Maranhão [168], Minas Gerais [169] and Rio Grande do Sul [170].…”
Section: Stomach Disordersmentioning
confidence: 99%